PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP MOTIVASI BELAJAR DAN HASIL BELAJAR PPKN SISWA KELAS V SD NEGERI 056587 PANTAI SAMPAH T.A 2021/2022 - Muhammad Ishaq (JURNAL TEMATIK, 2022)
This research is motivated by the low motivation and learning outcomes of fifth graders in Civics learning. The cause of the problem is the lack of creativity and innovation of teachers in learning. The make a match learning model is good to use when the teacher wants students' creativity and increases student learning motivation so that student learning outcomes can be optimal and learning becomes more effective. This research is a classroom action research to improve the learning outcomes of teacher reflection. The results showed that before being given the action (pre-cycle) the average student learning outcomes were 62 or 16.7%, after the first cycle was applied with the Make A Match Cooperative Learning Model, the average student learning outcomes increased to 78 or 66.7% of students who completed in learning, and then increased to an average of 86 after the second cycle was carried out so that as many as 96.7% of students finished learning. Then it is proven that there is an effect of the make a match learning model on the motivation and learning outcomes of fifth graders at SD Negeri 056587 Pantai Sampah in the Civics subject matter of Rights and Obligations for the academic year 2021/2022.